2023
DOI: 10.1021/acs.jafc.3c03552
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Induces Blood–Testis Barrier Dysfunction through Disrupting p38 Signaling Pathway-Mediated Tight Junction Protein Expression and Distribution in Mice

Chenjiao Miao,
Zijia Wang,
Xin Wang
et al.

Abstract: Deoxynivalenol (DON) is widely present in cereals and processed grains. It can disrupt the blood-testicular barrier (BTB), leading to sterility in males; however, the mechanism is unknown. In this study, 30 Kunming mice and TM4 cells were exposed to 0 or 4.8 mg/kg (28 d) and 0–2.4 μM (24 h) of DON, respectively. Histopathological findings showed that DON increased BTB permeability in mice, leading to tight junction (TJ) structural damage. Immunofluorescence results indicated that DON disrupted the localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Western blotting results showed that DON increased the ratio of GTP-RhoA/total RhoA as well as protein expression of ROCK and p53 in mice jejunal tissue, suggesting that DON-induced p53-dependent mitochondrial pathway apoptosis may be associated with activation of the RhoA/ROCK pathway in mice jejunum tissue. Furthermore, the RhoA/ROCK pathway directly phosphorylates MLC-2, leading to cytoskeletal contraction, which regulates the generation of apoptotic vesicles and the localized internalization of TJ proteins . Moreover, the RhoA/ROCK pathway mediates F-actin rearrangements through actin-binding proteins .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Western blotting results showed that DON increased the ratio of GTP-RhoA/total RhoA as well as protein expression of ROCK and p53 in mice jejunal tissue, suggesting that DON-induced p53-dependent mitochondrial pathway apoptosis may be associated with activation of the RhoA/ROCK pathway in mice jejunum tissue. Furthermore, the RhoA/ROCK pathway directly phosphorylates MLC-2, leading to cytoskeletal contraction, which regulates the generation of apoptotic vesicles and the localized internalization of TJ proteins . Moreover, the RhoA/ROCK pathway mediates F-actin rearrangements through actin-binding proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent staining of ZO-1 was performed with reference to previous methods. 24 Briefly, ZO-1 staining was performed using a primary antibody and a secondary antibody conjugated form. Mice jejunal tissue primary antibody was used with ZO-1 (1:1000, Servicebio, Wuhan, China).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations